Impact of Intraoperative Patient‐Specific 3D ‐Printed Temporal Bones: A Randomized Controlled Trial - Adam Omari; Obinna I. Nwosu; Steven A. W. Andersen; Alicia M. Quesnel (The Laryngoscope, 2026)
ABSTRACT Objective To determine if intraoperative inspection of patient‐specific 3D‐printed TB models, as a supplement to standard imaging, affects the cognitive load of surgeons during cochlear implantation (CI). Methods This randomized controlled trial included 40 consecutive adult primary CI surgeries performed by seven attending and five trainee surgeons at a large CI center. Cases were randomized 1:1 to current standard with surgical planning based on imaging review (controls) or to current standard plus intra‐operative inspection of a 3D‐printed model (intervention). The primary outcome, intraoperative cognitive load, was measured using the Surgery Task Load Index (Surg‐TLX) and analyzed with linear mixed‐effects models. Secondary outcomes included ratings of model anatomy, utility, and user experience (Schlegel‐questionnaire) and prediction of intraoperative challenges. Results Attending surgeons experienced lower overall cognitive load using 3D models versus controls (3.8 vs. 5.5; p < 0.01), driven by reduced physical fatigue ( p = 0.01). Conversely, residents reported higher overall load (7.2 vs. 4.8; p = 0.02) with increased mental ( p = 0.01) and physical fatigue ( p < 0.001). Fellows showed no significant difference in overall load (8.2 vs. 8.0; p = 0.88) but noted lower case complexity ( p = 0.02) offset by higher physical fatigue ( p = 0.04). Models were viewed as accurate and useful, particularly for trainee education, anticipating case difficulty and anatomical boundaries. Conclusion The clinical impact of intraoperative 3D‐printed models during CI is modulated by surgical experience. For attendings, models act as high‐fidelity references facilitating cognitive offloading, whereas they stimulate mental effort for trainees. Selective implementation is recommended to align use of models to surgical experience level to promote operative efficiency and surgical training. Level of Evidence Level II.